Multiple Sources of the Outbreak of Legionnaires’ Disease in Genesee County, Michigan, in 2014 and 2015 - Smith, Anya F. (Environ Health Perspect, 2019)
BACKGROUND: A community-wide outbreak of Legionnaires’ disease (LD) occurred in Genesee County, Michigan, in 2014 and 2015. Previous reports about the outbreak are conflicting and have associated the outbreak with a change of water source in the city of Flint and, alternatively, to a Flint hospital. OBJECTIVE: The objective of this investigation was to independently identify relevant sources of Legionella pneumophila that likely resulted in the outbreak. METHODS: An independent, retrospective investigation of the outbreak was conducted, making use of public health, health care, and environmental data and whole-genome multilocus sequence typing (wgMLST) of clinical and environmental isolates. RESULTS: Strong evidence was found for a hospital-associated outbreak in both 2014 and 2015: a) 49% of cases had prior exposure to Flint hospital A, significantly higher than expected from Medicare admissions; b) hospital plumbing contained high levels of L. pneumophila; c) Legionella control measures in hospital plumbing aligned with subsidence of hospital A-associated cases; and d) wgMLST showed Legionella isolates from cases exposed to hospital A and from hospital plumbing to be highly similar. Multivariate analysis showed an increased risk of LD in 2014 for people residing in a home that received Flint water or was located in proximity to several Flint cooling towers. DISCUSSION: This is the first LD outbreak in the United States with evidence for three sources (in 2014): a) exposure to hospital A, b) receiving Flint water at home, and c) residential proximity to cooling towers; however, for 2015, evidence points to hospital A only. Each source could be associated with only a proportion of cases. A focus on a single source may have delayed recognition and remediation of other significant sources of L. pneumophila. https://doi.org/10.1289/EHP5663